The impact of COVID-19 pandemic on small and medium enterprises in Bangladesh - Islam, Asadul; Rahman, Atiya; Nisat, Rafia (BRAC Institute of Governance and Development (BIGD), 2022)
Like other economic players, the novel pandemic severely hit small businesses—the larger source of growth and employment but also the most vulnerable sector—by disrupting national and international business networks, supply chain, and demand. To understand the evolving state of small enterprises during pre, par, and post-lockdown periods, BIGD in collaboration with Monash University, Australia conducted a survey on small enterprises, mostly light-engineering firms, and young workers across 18 districts in Bangladesh. The study finds that lockdown measures caused the majority of small enterprises to shut down, and during the early period of relaxing the lockdown, one-third of the enterprises were operating at limited capacity. Demand drop and the burden of fixed costs to run the businesses were the prominent reasons behind the drastic fall in profit. As a result, workers were losing jobs and the gender gap was widening, because female labour-intensive work (i.e. beauty parlour, tailoring) was affected harder. Other findings of concern include the emerging vulnerabilities for the enterprises with lower endowment and poor access to government stimulus packages and other financial support. The study emphasises on the importance of concrete targeting criteria and support delivery platforms to assist more vulnerable enterprises. Finally, it highlights that the enterprises that received BRAC’s intensive training on occupational health and safety (OHS), along with business training and financial linkages, made double profit compared to their counterparts. However, the absolute amount of profit was substantially lower for both groups, compared to their pre-COVID profit, indicating the importance of scaling up such intensive training to create more resilient enterprises in such crises.